Optical Activity of Metal Nanoclusters Deposited on Regular and Doped Oxide Supports from First-Principles Simulations - Luca Sementa (MDPI AG, 2021)
We report a computational study and analysis of the optical absorption processes of Ag20 and Au20 clusters deposited on the magnesium oxide (100) facet, both regular and including point defects. Ag20 and Au20 are taken as models of metal nanoparticles and their plasmonic response, MgO as a model of a simple oxide support. We consider oxide defects both on the oxygen anion framework (i.e., a neutral oxygen vacancy) and in the magnesium cation framework (i.e., replacing Mg++ with a transition metal: Cu++ or Co++). We relax the clusters’ geometries via Density-Functional Theory (DFT) and calculate the photo-absorption spectra via Time-Dependent DFT (TDDFT) simulations on the relaxed geometries. We find that the substrate/cluster interaction induces a broadening and a red-shift of the excited states of the clusters, phenomena that are enhanced by the presence of an oxygen vacancy and its localized excitations. The presence of a transition-metal dopant does not qualitatively affect the spectral profile. However, when it lies next to an oxygen vacancy for Ag20, it can strongly enhance the component of the cluster excitations perpendicular to the surface, thus favoring charge injection.